Drugging the 'undruggable'. Therapeutic targeting of protein–DNA interactions with the use of computer-aided drug discovery methods. Issue 11 (November 2021) - Radaeva, Mariia; Ton, Anh-Tien; Hsing, Michael; Ban, Fuqiang; Cherkasov, Artem
Highlights: There is a prevailing view that DNA-binding protein surfaces are not druggable. We argue that protein-DNA surfaces are druggable and provide examples. CADD helps to overcome challenges of protein-DNA interactions targeting. The development of protein-DNA inhibitors provides new strategies to combat cancer. Abstract: Transcription factors (TFs) act as major oncodrivers in many cancers and are frequently regarded as high-value therapeutic targets. The functionality of TFs relies on direct protein–DNA interactions, which are notoriously difficult to target with small molecules. However, this prior view of the 'undruggability' of protein–DNA interfaces has shifted substantially in recent years, in part because of significant advances in computer-aided drug discovery (CADD). In this review, we highlight recent examples of successful CADD campaigns resulting in drug candidates that directly interfere with protein–DNA interactions of several key cancer TFs, including androgen receptor (AR), ETS-related gene (ERG), MYC, thymocyte selection-associated high mobility group box protein (TOX), topoisomerase II (TOP2), and signal transducer and activator of transcription 3 (STAT3). Importantly, these findings open novel and compelling avenues for therapeutic targeting of over 1600 human TFs implicated in many conditions including and beyond cancer.